Entrepreneural competency of ecotourism business operators at Kuala Tahan National Park - Nor Din, Nur Aiman (2016)
The entrepreneurial competency is one of the most important requirements for the success of a small enterprise. Based on general studies, the total performance of the business is mainly determined by the attitudes, decisions and actions of the entrepreneur manager. This study was conducted with the main purpose of assessing entrepreneurial competency of business operator in Kuala Tahan and to profile the type of businesses operated by them. There were 57 respondents interviewed, guided by a set of questionnaire. Data analysis was carried out by using frequency analysis, index analysis and correlation analysis. From observation, there were variety of business carried out here it is accommodation, restaurant, guide, boat transportation, grocery, gift shop, and tourism agency. Results, show that the main business operated at Kuala Tahan are guest house, chalet, and restaurants. While result from the analysis show there exist a weak association between one independents variables which is self-confidence competency with the dependents variables it is educational level. The result also found that they have the higher score for attitude which is initiative, efficiency, and determination. However, the result also found that they have the attitude to be successful entrepreneur which is see and seize on opportunity, information seeking, emphasize on high quality of work, commitment to work, systematic planning, problem solving, and self-confidence but it still standing at the moderate level. The parties responsible such as The Ministry of Rural and Regional Development, Majlis Amanah Rakyat (MARA), and local authorities should play their roles more effectively and efficiently to help business operators to ensure that they have the adequate training and knowledge to cope with challenges in the business. It is recommended that the various government and private agencies should play more active role and actions to equip the small scale entrepreneurs with necessary managerial skills. So at the end, it could enhance their business performance and help them to more successful.